Association of Cerebral Amyloidosis, Blood Pressure, and Neuronal Injury with Late-life Onset Depression - Min Soo Byun; Young Min Choe; Bo Kyung Sohn; Dahyun Yi; Ji Young Han; Jinsick Park; Hyo Jung Choi; Hyewon Baek; Jun Ho Lee; Hyun-jung Kim; Yu Kyeong Kim; Eun Jin Yoon; et al. (Frontiers in Aging Neuroscience, 2016)
Previous literature suggests that Alzheimer’s disease (AD) process may contribute to late-life onset depression (LLOD). Therefore, we investigated the association of LLOD with cerebral amyloidosis and neuronal injury, the two key brain changes in AD, along with vascular risks. Twenty nine non-demented individuals who first experienced major depressive disorder (MDD) after age of 60 years were included as LLOD subjects, and 27 non-demented elderly individuals without lifetime experience of MDD were included as normal controls (NC). Comorbid mild cognitive impairment (MCI) was diagnosed in 48% of LLOD subjects and in 0% of NC. LLOD, irrespective of comorbid MCI diagnosis, was associated with prominent prefrontal cortical atrophy. Compared to NC, LLOD subjects with comorbid MCI (LLODMCI) showed increased cerebral 11C-Pittsburg compound B (PiB) retention and plasma beta-amyloid 1-40 and 1-42 peptides, as measures of cerebral amyloidosis; and, such relationship was not observed in overall LLOD or LLOD without MCI (LLODwoMCI). LLOD subjects, particularly the LLODwoMCI, had higher systolic blood pressure (SBP) than NC. When analyzed in the same multiple logistic regression model that included prefrontal gray matter (GM) density, cerebral amyloidosis and SBP as independent variables, only prefrontal GM density showed a significant independent association with LLOD regardless of MCI comorbidity status. Our findings suggest AD process might be related to LLOD via prefrontal neuronal injury in the MCI stage, whereas vascular processes—SBP elevation, in particular—are associated with LLOD via prefrontal neuronal injury even in cognitively intact or less impaired individuals.